128 Diagnostic Performance of the Components from the Multi-parametric Cardiovascular Magnetic Resonance Imaging Protocol: A Pre-defined CE-MARC Sub-study. (31st May 2014) - Greenwood, John; Ripley, David; Motwani, Manish; Brown, Julia; Nixon, Jane; Everett, Colin; Maredia, Neil; Bijsterveld, Petra; Plein, Sven
Abstract : Background: CE-MARC was the largest prospective evaluation of the diagnostic accuracy of CMR in coronary artery disease. CE-MARC adopted a multi-parametric protocol assessing ventricular function, myocardial perfusion, viability (with late gadolinium enhancement (LGE)) and coronary artery anatomy. Previous small studies have shown the diagnostic accuracy of different components of the CMR examination but with contrasting results. Methods: All patients from the CE-MARC population were studied. Visual CMR analyses were from the original, blinded read. Pre-specified sub-analysis of the individual core components of the CMR protocol was performed in isolation, as a paired component (perfusion and LGE) and as a triplet (perfusion, LGE and ventricular function) compared to the full multi-parametric protocol. Results: Both CMR and X-ray angiography were available in 676 patients. The diagnostic accuracy of the combined CMR protocol, individual components and paired and triplet combinations compared to the full multi-parametric protocol are presented in Table 1 and Figure 1 . The maximum sensitivity for the detection of significant CAD was achieved when all four components were used. No individual component, paired or triplet outperformed the multi-parametric protocol in terms of sensitivity. However in terms specificity, the individual components of perfusion, ventricular function and LGE all performed significantly better than the multi-parametric protocol (P < 0.0001). In addition, combining LGE with perfusion or with perfusion and ventricular function significantly improved the specificity compared to the full protocol (P < 0.0001). In terms of NPV the multi-parametric protocol performed better than all individual components, paired or triplet combination. Conclusion: A combined multi-parametric CMR protocol has higher sensitivity and NPV that the individual components however the specificity of the individual components of perfusion, ventricular function and late gadolinium enhancement (LGE) performed significantly better than the multi-parametric protocol.